Kompetensi Account Officer dan Informasi Asimetri terhadap Kinerja Murabahah dengan Risiko sebagai Variabel Intervening (Studi di BMT Kabupaten Banyuwangi dan Jember) - Brian Ahmad Nur Hasan; Ahmad Roziq; Imam Mas'ud (UPT Penerbitan Universitas Jember, 2017)
The aim of this research were to examine the influence of syariah account officer competency and asymmetry information formurabahah budgeting performance by using murabahah budgeting risk as intervening variable. The research sample was theBMT in Banyuwangi and Jember regency. This research used Partial Least Square (PLS) with purposive sampling 51respondents. The Results showed is syariah account officer competency was significant positively influence on the murabahahbudgeting performance variable. Asymmetry information was significant negatively influence on the murabahah budgetingperformance. So, syariah account officer competency was not influence on the murabahah budgeting risk variable. Fourth,asymmetry information was not influence on the murabahah budgeting risk. And last, murabahah budgeting risk wasinsignificant negatively influence on the murabahah budgeting performance.